Epidermal Growth Factor and Proliferation in Rat Hepatocytes in Primary Culture Isolated at Different Times after Partial Hepatectomy - Francavilla, Antonio (1986)
Primary hepatocyte cultures have been prepared from normal adult rat liver and from rat liver at 4, 8, 12, 24, and 48 h following partial hepatectomy (removal of 70% of the liver). Cells were maintained in minimal essential medium alone or supplemented with hormones. Comparing DNA synthesis in normal adult rat hepatocytes with DNA synthesis in hepatocytes isolated from regenerating livers, we found with minimal essential medium alone little DNA synthesis in normal adult rat hepatocytes and in hepatocytes isolated 4, 8, or 12 h after 70% hepatectomy. In hepatocytes isolated 24 h after partial hepatectomy, however, the incorporation of [(3)H]thymidine was 3 times the rate of normal hepatocytes. The addition of insulin to minimal essential medium had minimal effect on DNA synthesis in all hepatocytes. Addition of epidermal growth factor alone or in combination with insulin resulted in a dramatic increase in DNA synthesis in hepatocytes from regenerating rat liver. Increased incorporation was detectable as early as 4 h after partial hepatectomy and reached a maximum at 24 h after the operation. Results obtained with [(3)H]thymidine incorporation were confirmed by autoradiography and by direct DNA determinations in hepatocyte cultures. Epidermal growth factor binding to the hepatocytes was determined and agreed with previously reported binding studies. Binding of epidermal growth factor in hepatocytes isolated at 4 h after partial hepatectomy was the same as in normal hepatocytes but was undetectable in hepatocytes isolated from rats at 12 and 24 h after partial hepatectomy.